2022
DOI: 10.1038/s41467-022-28622-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of lattice dynamics in ferroelectric switching

Abstract: Reducing the switching energy of ferroelectric thin films remains an important goal in the pursuit of ultralow-power ferroelectric memory and logic devices. Here, we elucidate the fundamental role of lattice dynamics in ferroelectric switching by studying both freestanding bismuth ferrite (BiFeO3) membranes and films clamped to a substrate. We observe a distinct evolution of the ferroelectric domain pattern, from striped, 71° ferroelastic domains (spacing of ~100 nm) in clamped BiFeO3 films, to large (10’s of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 61 publications
1
19
0
1
Order By: Relevance
“…In particular, it has been shown that deposition of La 1−x Sr x MnO 3 via pulsed-laser deposition in low partial pressures of oxygen can drive high defect densities which allow coherent deposition of films to commercially available oxide substrates from LaAlO 3 (pseudocubic lattice parameter of 3.78 Å) to NdScO 3 (4.00 Å) [103]. As such, this has enabled the deposition of epitaxial films of large latticeparameter FEs including BaTiO 3 and 0.68PbMg 1/3 Nb 2/3 O 3 -0.32PbTiO 3 [102], in addition to PbZr 0.2 Ti 0.8 O 3 (PZT) [101] and BiFeO 3 [104].…”
Section: Chemical Lift-offmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, it has been shown that deposition of La 1−x Sr x MnO 3 via pulsed-laser deposition in low partial pressures of oxygen can drive high defect densities which allow coherent deposition of films to commercially available oxide substrates from LaAlO 3 (pseudocubic lattice parameter of 3.78 Å) to NdScO 3 (4.00 Å) [103]. As such, this has enabled the deposition of epitaxial films of large latticeparameter FEs including BaTiO 3 and 0.68PbMg 1/3 Nb 2/3 O 3 -0.32PbTiO 3 [102], in addition to PbZr 0.2 Ti 0.8 O 3 (PZT) [101] and BiFeO 3 [104].…”
Section: Chemical Lift-offmentioning
confidence: 99%
“…The substrate clamping effect has been extensively studied in FE films [194,195], as a limiting factor for their piezoresponse as well as for their poling ability, which plays a significant role in the thickness scalability of these materials and the energy required to activate polarization-switching processes. The role of the mechanical boundary conditions on the energetics and lattice dynamics of these systems was explored in detail in BaTiO 3 [102] and BiFeO 3 [104] capacitors fabricated on silicon after epitaxial lift-off and transfer. These works revealed how the removal of substrate bonding strongly alters the FE switching paths by facilitating structural distortions upon voltage application that were restricted by the substrate-imposed mechanical constraint.…”
Section: Improved Performance In Transferred Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from providing further methods of strain control, it was found that the freestanding membranes had markedly increased switching speeds and reduced coercive fields, pointing to the significant role that elastic constraints can play in ferroelectric switching processes and warranting further study. [ 246 ] Utilizing freestanding membranes of oxide ferroelectrics is still in its infancy, and researchers are envisioning new experiments in hybrid epitaxy to combine perovskite and nonperovskite layers to achieve new ferroic coupling, for example, magnetoelectric coupling, [ 247 ] as well as novel Moire pattern physics in oxide systems. [ 248 ]…”
Section: Advanced Epitaxy and Beyondmentioning
confidence: 99%
“…For three-dimensional compounds there has been a vivid search for new ferroelectrics with optimal properties. For example with respect to lead-free energy storage materials [33] or low switching barriers for memory applications [34]. To this end, high throughput DFT calculations has proven a powerful strategy that can be used to rapidly screen thousands of materials for desired properties.…”
Section: Introductionmentioning
confidence: 99%